2018
DOI: 10.1016/j.neuron.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptojanin and Endophilin Mediate Neck Formation during Ultrafast Endocytosis

Abstract: Ultrafast endocytosis generates vesicles from the plasma membrane as quickly as 50 ms in hippocampal neurons following synaptic vesicle fusion. The molecular mechanism underlying the rapid maturation of these endocytic pits is not known. Here we demonstrate that synaptojanin-1, and its partner endophilin-A, function in ultrafast endocytosis. In the absence of synaptojanin or endophilin, the membrane is rapidly invaginated, but pits do not become constricted at the base. The 5-phosphatase activity of synaptojan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 72 publications
(153 reference statements)
9
123
0
Order By: Relevance
“…However, the Drosophila model revealed loss of dopaminergic neurons, providing evidence for the contribution of synaptic autophagy defects in pathogenesis of PD (Vanhauwaert et al ). Considering its dual enzymatic activity, SynJ1 is also believed to play a role in fast endophilin‐mediated, clathrin‐independent endocytosis which is an alternative to CME (Watanabe et al ) and several other processes. It remains to be determined if SYNJ1 exert its effects on PD pathogenesis through any of the alternative endocytic pathways.…”
Section: Clathrin‐mediated Synaptic Vesicle Endocytosis: a Prime Target?mentioning
confidence: 99%
“…However, the Drosophila model revealed loss of dopaminergic neurons, providing evidence for the contribution of synaptic autophagy defects in pathogenesis of PD (Vanhauwaert et al ). Considering its dual enzymatic activity, SynJ1 is also believed to play a role in fast endophilin‐mediated, clathrin‐independent endocytosis which is an alternative to CME (Watanabe et al ) and several other processes. It remains to be determined if SYNJ1 exert its effects on PD pathogenesis through any of the alternative endocytic pathways.…”
Section: Clathrin‐mediated Synaptic Vesicle Endocytosis: a Prime Target?mentioning
confidence: 99%
“…Although a central role of CME in synaptic vesicle protein retrieval from the plasma membrane was proposed , later research revealed that CME is not essential for the maintenance of synaptic vesicles and neurotransmission . Furthermore, fast acting recycling mechanisms have been shown to be clathrin‐independent in neurons as well as in other mammalian cells . Nevertheless, CME plays a key role in regenerating synaptic vesicles from synaptic endosomes after ultrafast endocytosis (UFE) and bulk endocytosis (but also see [PMID 24963135]).…”
Section: Synaptic Vesicle Endocytic Pathways and Their Regulation By mentioning
confidence: 99%
“…This pathway operates at a faster pace than CME (a few seconds compared to 30 s to a minute) and it has been termed fast endophilinmediated endocytosis (FEME, [54,64]) in non-neuronal mammalian cells. Endophilins, and possibly FEME, also regulate the number of synaptic vesicles and synaptic vesicle endocytosis at peripheral (neuromuscular junction) and central (hippocampal) synapses [53,57,65]. During UFE, endophilin works together with synaptojanin to accelerate the speed of endocytosis via regulation of neck formation in membrane invaginations and subsequently they regulate clathrin uncoating after vesicle reformation for synaptic endosomes [53] (also see [57,65]).…”
Section: Synaptic Vesicle Endocytic Pathways and Their Regulation By mentioning
confidence: 99%
See 1 more Smart Citation
“…A was first attributed to play a role in fast bulk endocytosis, but with slower kinetics than that of 471 ultrafast endocytosis (Watanabe & Boucrot, 2017). More recently, endophilin A and synaptojanin were 472 found to accelerate ultrafast endocytosis at hippocampal synapses (Watanabe et al, 2018). In Cm 473 recordings of endophilin A knock-out IHCs no apparent increase in Cm was observed (Kroll et al, 2019), 474 seemingly arguing against an involvement of endophilin A in ultrafast endocytosis at this synapse.…”
Section: What Other Molecular Players Could Be Involved In Ultrafast mentioning
confidence: 99%